Development and initial validation of a novel undercut thread design for locking screws. Issue 7 (July 2022) - Feng, Xiaoreng; Zhang, Sheng; Liang, Hongfeng; Chen, Bin; Leung, Frankie
Highlights: The undercut thread described in this study is specially designed for the loading condition of the locking screw. The novel undercut threaded locking screw showed better fixation stability than the typical buttress threaded locking screw. This novel thread design reduces screw failure rate in osteoporosis trabecular bone and provides a new thread choice for osteoporotic bone. Abstract: Background: Locking screws with a typical buttress thread have high levels of failure in patients with osteoporotic bones. This study aims to develop a novel thread design for the locking screw and compare its fixation stability with the typical buttress thread. Methods: Locking screws with a novel thread design that possess an undercut feature and locking screws with a typical buttress thread were manufactured from stainless steel. Their fixation stabilities were then evaluated individually under a lateral migration test and evaluated in pairs together with a locking plate (LP) in an osteoporotic bone substitute under cyclic craniocaudal and torsional loadings. A finite element analysis (FEA) model was constructed to analyze the stress distributions present in the bone tissue adjacent to the novel thread versus the buttress thread. Results: The biomechanical test revealed that the novel thread had a significantly higher lateral migration strength than the buttress thread. When applied to a LP, the locking screw with the novel thread requires more cycles and higher forces or torque to resist migration up to 5 mm or 10° than the buttress thread. The FEA simulation showed that the novel thread can make the stress distribute more evenly at the adjacent bone tissue when compared with the buttress thread. Conclusions: The locking screw with the novel undercut thread had superior lateral migration resistance during both initial and continued migration and superior fixation stability when applied to a LP under both cyclic craniocaudal loading and torsional loading than the locking screw with a typical buttress thread.